Presentation and Diagnosis of Pediatric X-Linked Hypophosphatemia - Kento Ikegawa; Yukihiro Hasegawa (Endocrines, 2023)
X-linked hypophosphatemia (XLH) is a rare type of hereditary hypophosphatemic rickets. Patients with XLH have various symptoms that lower their QOL as defined by HAQ, RAPID3, SF36-PCS, and SF36-MCS in adult patients and SF-10 and PDCOI in pediatric patients. Early diagnosis and treatment are needed to reduce the burden, but the condition is often diagnosed late in childhood. The present review aims to summarize the symptoms, radiological and biological characteristics, and long-term prognosis of pediatric XLH. Typical symptoms of XLH are lower leg deformities (age six months or later), growth impairment (first year of life or later), and delayed gross motor development with progressive lower limb deformities (second year of life or later). Other symptoms include dental abscess, bone pain, hearing impairment, and Chiari type 1 malformation. Critical, radiological findings of rickets are metaphyseal widening, cupping, and fraying, which tend to occur in the load-bearing bones. The Rickets Severity Score, validated for XLH, is useful for assessing the severity of rickets. The biochemical features of XLH include elevated FGF23, hypophosphatemia, low 1,25(OH)2D, and elevated urine phosphate. Renal phosphate wasting can be assessed using the tubular maximum reabsorption of phosphate per glomerular filtration rate (TmP/GFR), which yields low values in patients with XLH. XLH should be diagnosed early because the multisystem symptoms often worsen over time. The present review aims to help physicians diagnose XLH at an early stage.